2008
DOI: 10.1016/j.stem.2008.07.024
|View full text |Cite
|
Sign up to set email alerts
|

JNK Activity in Somatic Stem Cells Causes Loss of Tissue Homeostasis in the Aging Drosophila Gut

Abstract: Metazoans employ cytoprotective and regenerative strategies to maintain tissue homeostasis. Understanding the coordination of these strategies is critical to develop accurate models for aging and associated diseases. Here we show that cytoprotective Jun-N-terminal Kinase (JNK) signaling influences regeneration in the Drosophila gut by directing proliferation of intestinal stem cells (ISCs). Interestingly, this function of JNK contributes to the loss of tissue homeostasis in old and stressed intestines by promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
710
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(755 citation statements)
references
References 47 publications
40
710
2
3
Order By: Relevance
“…Reduced stem cell proliferation was observed both during normal homeostasis (Fig 2A and B) and in response to epithelial damage [damage induced by dextran sodium sulphate (DSS; Amcheslavsky et al , 2009), Fig 2C and D]. Ret downregulation or mutation also reduced the epithelial hyperplasia observed during normal ageing (Biteau et al , 2008; Choi et al , 2008; Fig 2F and G). Additional cell type‐specific quantifications revealed that this reduction in stem cell proliferation did not result from stem cell loss, nor was it accompanied by abnormal differentiation of their progeny.…”
Section: Resultsmentioning
confidence: 93%
“…Reduced stem cell proliferation was observed both during normal homeostasis (Fig 2A and B) and in response to epithelial damage [damage induced by dextran sodium sulphate (DSS; Amcheslavsky et al , 2009), Fig 2C and D]. Ret downregulation or mutation also reduced the epithelial hyperplasia observed during normal ageing (Biteau et al , 2008; Choi et al , 2008; Fig 2F and G). Additional cell type‐specific quantifications revealed that this reduction in stem cell proliferation did not result from stem cell loss, nor was it accompanied by abnormal differentiation of their progeny.…”
Section: Resultsmentioning
confidence: 93%
“…While this review will focus on stem cell aging in mammals, it is important to note that elegant studies in invertebrates have highlighted the changes in stem cell and niche during aging, and the mechanisms underlying some of these changes (Arantes-Oliveira et al, 2002;Boyle et al, 2007;Jones, 2007;Biteau et al, 2008). In mammals, age-related changes to stem cells and their niches may be broadly grouped into two classes: those that are irreversible versus reversible in nature (Figure 1).…”
Section: Defects In Number In Aging Stem Cellsmentioning
confidence: 99%
“…Phenotypes such as ISCs hyperproliferation, cell lineage misdifferentiation and defective epithelial barrier and absorption functions characterize the ageing Drosophila midgut (Biteau et al, 2008) (Rera et al, 2012) (Choi et al, 2008) ( Figure 3C). …”
Section: Ageing and Intestinal Stem Cell Homeostasismentioning
confidence: 99%
“…Hyperactivation of the JNK-dependent stress response has been shown to be a main factor inducing age related hyperplasia in the Drosophila intestine, while exacerbated Notch signalling partly contributes to mis-differentiation (Biteau et al, 2008). Deregulation of additional pathways previously linked to the stress and damage response, such as components of the ROS and Wg/Myc signalling have also been associated with loss of homeostasis in the ageing Drosophila midgut (Wang et al, 2014) (Cordero et al, 2012b).…”
Section: Ageing and Intestinal Stem Cell Homeostasismentioning
confidence: 99%